In situ investigation of annealing effect on thermophysical properties of single carbon nanocoil. (April 2020) - Deng, Chenghao; Cong, Tianze; Xie, Yangsu; Wang, Ridong; Wang, Tianyu; Pan, Lujun; Wang, Xinwei
Highlights: Reported the first time in-situ thermal characterization study of individual carbon nanocoil after current-induced annealing. The reaction rate during annealing was found have a normal distribution against the annealing power. From 1200 K to 1800 K, the thermal conductivity of an individual carbon nanocoil has a 8.7-fold increase. A linear relationship was found between thermal diffusivity and electrical conductivity during annealing. A linear relationship was discovered between the inverse of thermal conductivity and annealing temperature. Abstract: In reported high-temperature annealing of carbon nanocoils (CNCs), the samples studied before and after annealing are different ones. This significantly hinders annealing effect understanding due to unknown and remarkable sample-to-sample structure difference. Here using the transient electro-thermal technique (TET) and current-induced annealing, we report the first time in situ investigation of annealing effect on the thermophysical properties for the same individual CNC. Our dynamic annealing track uncovers an electrical resistance relation with annealing time as R ∼ − R s ln ( t ) . The reaction rate ( Rs) shows a normal distribution against the annealing power/temperature, proposing that the activation energy for structure reconstruction in CNCs follows a normal distribution. After annealing at 5–35€μA, the average thermal diffusivity ( α ) and electrical conductivity ( σ ) of CNCs show respective 50–160% and 100–170% increase. Normative linear relation between α and σ is discovered, which proposes axial-direction parallel structure in CNCs. The nonuniform temperature distribution along the sample during annealing creates different annealing levels and provides a great advantage to study the relation between structure and thermophysical properties. Our micro-scale Raman characterization reveals the nonuniform distribution of grain size along the length direction of CNCs after annealing and finds a rapid grain size increase from 4.0 to 7.8 nm near the sample's middle point. The middle point of the sample has the highest temperature rise ( T c ), largest thermal conductivity ( κ ) increase, and the most dramatic structure improvement. Its κ shows a rapid improvement (8.7-fold maximum change) from 1200 K to 1800 K. A linear relation between κ −1 and T c is observed and is attributed to the change of grain size during annealing. Using the concept of thermal reffusivity (Θ=1/ α ), a 1-fold increase of average grain size and a 197 K decrease of Debye temperature of CNCs after annealing are uncovered.